(untitled) (Revista Brasileña de Terapia Comportamental y Cognitiva, 2007)
Verbal Behavior (VB) was the most important Skinner’s work. Generic self-analysis of the behavior registered on VB appears in its final parts and in others of the author’s books. This paper describes the functions of two specific under-classes of quoting episodes with transcription from other author’s text emitted by Skinner on VB. It deals with a historical research of the VB as the register of Skinner’s verbal behavior. From the general description of quoting with transcription, it establishes a functional analysis of two distinct under-classes by its autoclitic frame, according to a behavioral hermeneutics: a method that instructs a description of the controls on the interpretation. The formal-functional variations of quoting are informed: accurate verbal stimuli evocated the “argumentative” quoting (emitted with descriptive autoclitics) and the non-accurate, the “counter-argumentative” ones (emitted with manipulative and/or negation autoclitics). Despite of the difficulty in discriminating all controls on the interpretation, the paper shows the functional consistency of some the devices of persuasion in the Skinnerian rhetoric.